Surveying the Impact of Rarely Investigated Design Components on User Engagement - Saranya, Konudula Naga; Bhandari, Moksha; Borad, Neel; Reddy, Pollaggari Vamshi Pavan; Kumar , Santosh (University of Science and Computer Technology, 2025)
The rise of social media has transformed digital interaction, making user engagement a critical metric for platform success. While much research has examined conventional design elements such as layout and typography, the influence of rarely studied micro-design components remains underexplored. This study investigates the impact of micro-interactions, transition effects, and haptic feedback on user engagement. Using a quantitative survey method, data were collected from 400 active social media users who spend at least five hours weekly on digital platforms. The research employed a Likert-scale questionnaire combined with platform analytics to assess perceived usability and actual behavioral metrics. Results show that 73.5% of respondents experienced increased engagement through micro-interactions, while 68.2% found transition effects beneficial for smoother navigation. Although haptic feedback received less preference (56.8%), it enhanced multisensory interaction, especially among mobile users. Statistically, these components contributed to a 15.8% increase in session duration and significant improvements in engagement metrics—likes (25.4%), comments (47.6%), and content shares (66.7%). Regression and factor analysis confirmed the positive influence of all three design variables. This study contributes to the field of UI/UX by highlighting how overlooked micro-design elements can shape user behavior and improve platform interaction quality. The findings offer practical guidance for designers and developers to enhance user experience through subtle yet impactful interface innovations. Future research should explore adaptive and AI-driven design features to further personalize digital engagement.